Experimental and numerical studies of two arterial wall delamination modes. (January 2018) - Leng, Xiaochang; Zhou, Boran; Deng, Xiaomin; Davis, Lindsey; Lessner, Susan M.; Sutton, Michael A.; Shazly, Tarek
Abstract: Arterial wall dissection, which results from various pathophysiological processes, can lead to the occurrence of large area delamination in the aortic wall that can potentially block blood flow and lead to deleterious clinical conditions. Despite its critical clinical relevance, few studies have focused on investigating the failure mode of delamination in the arterial wall. In this study, we quantify the energy release rate of the medial layer of a porcine abdominal aorta via two delamination experiments: the mixed-mode delamination experiment and the "T"-shaped delamination experiment. A cohesive zone model (CZM) is applied to simulate the arterial wall delamination and Holzapfel-Gasser-Ogden (HGO) material model is used to capture the bulk arterial material behavior. A set of parameter values for the HGO and CZM models are identified through matching simulation predictions of the load vs. load-point displacement curve with experimental measurements. Then the parameter values and critical energy release rates obtained from experiments are used as input data for simulation predictions for two arterial wall delamination experiments. The simulation predictions show that the delamination front matches well with experimental measurements. Moreover, the mixed-mode delamination experiment reveals a shear mode-dominated failure event, whereas the "T"-shaped delamination experiment is an opening failure process. The integration of experimental data and numerical predictions of arterial delamination events provides a comprehensive description of distinct failure modes and aids in the prediction of aortic dissection.